The Storm Makers - Smith, Jennifer E., 1980- (Little, Brown and Company, 2012)
Twelve-year-olds Ruby and Simon have been growing apart since their parents moved them to a Wisconsin farm, but weird weather events that seem tied to Simon's emotions bring a stranger into their lives who introduces them to the Makers of Storms Society, strengthening the bond between the twins.